A 18p11.23-p11.31 microduplication in a boy with psychomotor delay, cerebellar vermis hypoplasia, chorioretinal coloboma, deafness and GH deficiency. Issue 1 (December 2016) - Giordano, Mara; Muratore, Valentina; Babu, Deepak; Meazza, Cristina; Bozzola, Mauro
Abstract Background Rearrangements involving the short arm of chromosome 18 have been extensively described. Here we report a microduplication of 320.5–431.5 Kb at 18p11.31-p11.23 in a 10 year-old boy. Case presentation In a 10 year-old boy with moderate psychomotor delay, hypoplasia of the cerebellar vermis, chorioretinal coloboma, deafness and growth hormone deficiency (GHD), an interstitial microduplication at 18p11.31-p11.23 was identified by array-CGH. This maternally inherited microduplication, encompasses three genes, namelyARHGAP28, LINC00668 andLAMA1 (a gene involved in cerebellum and retinal development). Conclusions The genotype-phenotype is discussed with particular attention to theLAMA1 gene, although it is difficult, as in many other similar situations, to assess the causality of the detected duplication in the absence of further studies aiming to explore the presence of co-occurring variants that could explain the incomplete penetrance.